2022
DOI: 10.3390/jcm11237140
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Growth Stagnation and Premature LH Surge Are the Keys to Obtaining a Viable Embryo in Monofollicular IVF Cycles: A Retrospective Cohort Study

Abstract: How LH levels influenced the outcomes of monofollicular IVF cycles using different stimulation protocols was controversial. In this single-center, retrospective study, we analyzed 815 monofollicular IVF cycles between 2016–2022 using natural cycle (NC), medroxyprogesterone acetate (MPA) or clomiphene citrate (CC) in addition to human menopausal gonadotropin (hMG), with or without GnRH antagonist. A viable embryo was obtained in 35.7% of all cycles. Growth stagnation and premature LH surge are two markedly nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In terms of premature LH surge rate, the two strategies showed a similar result (23.1% vs 25.2%, P=0.730), but the women in our study seem more likely to have premature LH surge during COS compared with previous studies ( 15 17 ). Numerous studies have reported low serum LH level ( 18 , 19 ), as well as high serum LH level during COS ( 9 , 19 ), would impair pregnancy and live birth outcomes. When it comes to the choice of GnRH-ant initiation strategy, according to previous studies, the inhibition effect of GnRH-ant on LH level did not differ between fixed or flexible GnRH-ant protocols, which are in accordance with our results ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of premature LH surge rate, the two strategies showed a similar result (23.1% vs 25.2%, P=0.730), but the women in our study seem more likely to have premature LH surge during COS compared with previous studies ( 15 17 ). Numerous studies have reported low serum LH level ( 18 , 19 ), as well as high serum LH level during COS ( 9 , 19 ), would impair pregnancy and live birth outcomes. When it comes to the choice of GnRH-ant initiation strategy, according to previous studies, the inhibition effect of GnRH-ant on LH level did not differ between fixed or flexible GnRH-ant protocols, which are in accordance with our results ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%